Promoting mobility and reducing length of stay in hospitalized general medicine patients: A quality‐improvement project. Issue 5 (5th February 2016) - Hoyer, Erik H.; Friedman, Michael; Lavezza, Annette; Wagner‐Kosmakos, Kathleen; Lewis‐Cherry, Robin; Skolnik, Judy L.; Byers, Sherrie P.; Atanelov, Levan; Colantuoni, Elizabeth; Brotman, Daniel J.; Needham, Dale M.
Abstract : OBJECTIVE: To determine whether a multidisciplinary mobility promotion quality‐improvement (QI) project would increase patient mobility and reduce hospital length of stay (LOS). PATIENTS AND METHODS: Implemented using a structured QI model, the project took place between March 1, 2013 and March 1, 2014 on 2 general medicine units in a large academic medical center. There were 3352 patients admitted during the QI project period. The Johns Hopkins Highest Level of Mobility (JH‐HLM) scale, an 8‐point ordinal scale ranging from bed rest (score = 1) to ambulating ≥250 feet (score = 8), was used to quantify mobility. Changes in JH‐HLM scores were compared for the first 4 months of the project (ramp‐up phase) versus 4 months after project completion (post‐QI phase) using generalized estimating equations. We compared the relative change in median LOS for the project months versus 12 months prior among the QI units, using multivariable linear regression analysis adjusting for 7 demographic and clinically relevant variables. RESULTS: Comparing the ramp‐up versus post‐QI phases, patients reaching JH‐HLM's ambulation status increased from 43% to 70% ( P < 0.001), and patients with improved JH‐HLM mobility scores between admission and discharge increased from 32% to 45% ( P < 0.001). For all patients, the QI project was associated with an adjusted median LOS reduction of 0.40 (95% confidence interval [CI]: −0.57 to −0.21, P  < 0.001) days compared to 12 months prior. A subgroup of patients expected to have a longer LOS (expected LOS >7 days), were associated with a significantly greater adjusted median reduction in LOS of 1.11 (95% CI: −1.53 to −0.65, P < 0.001) days. Increased mobility was not associated with an increase in injurious falls compared to 12 months prior on the QI units ( P = 0.73). CONCLUSIONS AND RELEVANCE: Active prevention of a decline in physical function that commonly occurs during hospitalization may be achieved with a structured QI approach. In an adult medicine population, our QI project was associated with improved mobility, and this may have contributed to a reduction in LOS, particularly for more complex patients with longer expected hospital stay. Journal of Hospital Medicine 2016. © 2016 Society of Hospital Medicine